Inhibition of monoacylglycerol lipase terminates diazepam‐resistant status epilepticus in mice and its effects are potentiated by a ketogenic diet. (24th November 2017) - Terrone, Gaetano; Pauletti, Alberto; Salamone, Alessia; Rizzi, Massimo; Villa, Bianca R.; Porcu, Luca; Sheehan, Mark J.; Guilmette, Edward; Butler, Christopher R.; Piro, Justin R.; Samad, Tarek A.; Vezzani, Annamaria
Summary: Objective: Status epilepticus (SE) is a life‐threatening and commonly drug‐refractory condition. Novel therapies are needed to rapidly terminate seizures to prevent mortality and morbidity. Monoacylglycerol lipase (MAGL) is the key enzyme responsible for the hydrolysis of the endocannabinoid 2‐arachidonoylglycerol (2‐AG) and a major contributor to the brain pool of arachidonic acid (AA). Inhibiting of monoacylglycerol lipase modulates synaptic activity and neuroinflammation, 2 mediators of excessive neuronal activation underlying seizures. We studied the effect of a potent and selective irreversible MAGL inhibitor, CPD‐4645, on SE that was refractory to diazepam, its neuropathologic sequelae, and the mechanism underlying the drug's effects. Methods: Diazepam‐resistant SE was induced in adult mice fed with standard or ketogenic diet or in cannabinoid receptor type 1 (CB1) receptor knock‐out mice. CPD‐4645 (10 mg/kg, subcutaneously) or vehicle was dosed 1 and 7 h after status epilepticus onset in video–electroencephalography (EEG) recorded mice. At the end of SE, mice were examined in the novel object recognition test followed by neuronal cellloss analysis. Results: CPD‐4645 maximal plasma and brain concentrations were attained 0.5 h postinjection (half‐life = 3.7 h) and elevated brain 2‐AG levels by approximately 4‐fold. CPD‐4645 administered to standard diet–fed mice progressively reduced spike frequency during 3 h postinjection, thereby shortening SE duration by 47%. The drug immediately abrogated SE in ketogenic diet–fed mice. CPD‐4645 rescued neuronal cell loss and cognitive deficit and reduced interleukin (IL)‐1β and cyclooxygenase 2 (COX‐2) brain expression resulting from SE. The CPD‐4645 effect on SE was similar in mice lacking CB1 receptors. Significance: MAGL represents a novel therapeutic target for treating status epilepticus and improving its sequelae. CPD‐4645 therapeutic effects appear to be predominantly mediated by modulation of neuroinflammation.